Predicting the environmental impact of structural systems with parameterization: Development of a design tool for the early design stages - Flyman, Robin (My University, 2024)
With the increasingly alarming threat from global warming, there is an urgent need to reduce the CO2 emissions across all sectors. With 38% of the emissions globally and 21% in Sweden, there is a great potential to reduce the carbon footprint of the construction sector. The emissions from a building are split into embodied and operational carbon, where new laws and regulations in Sweden will start targeting the embodied carbon in buildings. In Sweden, the structural system accounts for half of the embodied carbon in a building on average. The current procedure of conducting a life cycle assessment is often time-consuming and not suitable for early design stages, where there are many uncertainties. Designers need to have a holistic view when considering the emissions of a structural system, as optimising one part can increase the emissions from other parts of the system. In this thesis, a parametric tool was developed to address these points; uncertainties in the early stages, time constraints and limited knowledge regarding how the interplay is between the environmental impact and the parameters that controls the design of the structural system. The parametric tool has an emphasis on structural design, where the aim is to generate structural systems and predict the environmental impact at early stages, where the most impact can be achieved to the lowest cost. This tool models a framed structural system with columns, beams, and slabs, then performs a load takedown. The modular design of the tool allows it to be modified or expanded in the future. The parametric tool uses pre-calculated elements to design the structural system, after which it calculates and display the environmental impact to the user in a comprehensive way. Optimisation algorithms can be used to find some of the most optimised design alternatives for the given objectives. A case study has been performed to verify the performance and accuracy of the tool. The results from the case study showed that the tool will select similar cross sections as a structural engineer in the preliminary design stages, resulting in comparable carbon emissions. It was challenging to compare the emissions for the structural system between the reference building and the system generated by the tool, as the reference building included load bearing walls, which is not included in the tool at this stage. The tool could be further developed by including load-bearing walls, foundation, and horizontal stabilisation.
Keywords: Structural systems, embodied carbon, decarbonize, simplified life cycle assessment, early stage design, topology optimisation, multi-objective optimisation, parametric design, Grasshopper